Preliminary study on morphological characteristics of araceae species using phenetic approach / Liliwirianis Nawi ... [et al.] - Nawi, Liliwirianis; Musa, Nor Lailatul Wahidah; Md Isa, Nurun Nadhirah; Mohd Jan, Sarah Laila; Shaikh Nasir, Nur Thabitah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Araceae is a large family consisting Aroids or Arums. It is a monocot plants characterised by the inflorescence consisting of spadix subtending a spathe. The aim of the study was to determine the relationship of 13 species from seven genera of Araceae using phenetic approach. The seven genera are Anthurium, Spathyphyllum, Monstera, Philodendron, Syngonium, Alocasia and Caladium. A cluster analysis was performed using the Multivariate Statistical Procedures Version 2.2 (MVSP) on 22 morphological characters of selected species. Based on the similarity of morphological characters, these 13 species are clustered into three groups: (1) Anthurium forgetii and A. leuconeurum, (2) M. oblique expilata, P. scandens oxycardium and Monstera sp. 1 and, (3) M. deliciosa, P. scandens and Philodendron sp. 1. The cluster analysis indicates Caladium sp. 1 had the lowest similarities (5.6%) compared to other 12 species. Meanwhile, M. deliciosa and P. scandens exhibit the highest similarity (68.4%) for both analyses.